2018
DOI: 10.1093/rheumatology/key133
|View full text |Cite
|
Sign up to set email alerts
|

Lowering the recurrence rate in pigmented villonodular synovitis: A series of 120 resections

Abstract: In diffuse-type pigmented villonodular synovitis, total synovectomy might be difficult to achieve. As shown in our results and also in the literature, meticulous open resection, especially in difficult to approach areas such as the popliteal space, reduces local recurrence rates. External beam radiation is an option in prevention of otherwise non-operable local recurrences or in non-operable disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 14 publications
0
21
0
4
Order By: Relevance
“…Radiosynoviorthesis is the topical use of radioactive materials (most commonly 90yttrium) to restore the synovium as adjuvant or alternative therapy for surgery. [ 5 , 13 , 14 , 25 , 29 ] However, the use of ROS has many disadvantages, including the potential risk of early-onset arthritis, avascular necrosis, difficult surgical wound healing, and other surgical complications, and requiring specialized radiotherapy delivery systems and surgery due to resource-intensive and invasive. EBR (such as 3-dimensional conformal radiation therapy and IMRT) is noninvasive and needs a widely used CT planning system and linear accelerator.…”
Section: Review Of Literature and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiosynoviorthesis is the topical use of radioactive materials (most commonly 90yttrium) to restore the synovium as adjuvant or alternative therapy for surgery. [ 5 , 13 , 14 , 25 , 29 ] However, the use of ROS has many disadvantages, including the potential risk of early-onset arthritis, avascular necrosis, difficult surgical wound healing, and other surgical complications, and requiring specialized radiotherapy delivery systems and surgery due to resource-intensive and invasive. EBR (such as 3-dimensional conformal radiation therapy and IMRT) is noninvasive and needs a widely used CT planning system and linear accelerator.…”
Section: Review Of Literature and Discussionmentioning
confidence: 99%
“…Only one study reported necrosis of the femoral condyle due to repeated ROS treatmen. [ 5 ] Because ROS is resource-intensive and invasive, it requires specialized radiotherapy delivery systems and surgical procedures. However, EBRT is noninvasive and only needs the widely used CT planning system and linear accelerator.…”
Section: Review Of Literature and Discussionmentioning
confidence: 99%
“…The diffuse form of the disease, incomplete resection, the lesions being located in locations difficult to access, the surgeon having limited experience and skills, and the administration of adjuvant therapy after surgery have been identified as the major risk factors for recurrence [27]. Approximately two-thirds of local recurrences are diagnosed within postoperative 2 years, while less than 10% of recurrences are found after 3 years, and it is recommended that follow-up MRI scans are performed every 6 months during the first 3 years to detect local recurrences effectively [36]. In this patient, we successfully performed open complete excision.…”
Section: Discussionmentioning
confidence: 99%
“…[37] Nevertheless, it has been widely agreed that arthroscopic surgery has better functional results and less postoperative complications than that of open surgery. [37,38] A previous report found that, for the intra-articular lesions complicated with extracapsular posterior disease, anterior arthroscopic surgery combined with posterior open synovectomy was more effective than a single synovectomy. [39] Mollon et al also found that a combination of arthroscopic and open surgery Fang and Zhang Medicine (2020) 99: 16 Medicine might allow for more thorough removal and is applicable to all tumor resection while limiting patient morbidity, especially for high-risk situations associated with both intra-and extraarticular extension.…”
Section: Review Of Literature and Discussionmentioning
confidence: 99%
“…Research has shown that two-thirds of local recurrence were diagnosed during the first 2 years and <10% after 3 years, and follow-up MRI every 6 months during the first 3 years might be able to detect >90% of all local recurrences. [38] Therefore, in order to detect recurrence in time, regular and timely follow-up is required.…”
Section: Review Of Literature and Discussionmentioning
confidence: 99%